Financial and Business Advisory Services for Small and Medium Enterprises and Entrepreneurs in Agribusiness in Serbia - Jovin, Slobodanka S.; Eremić Đođić, Jelica; Laban, Bogdan; Milić, Dragana (Industrija, 2017)
Small and Medium-sized Enterprises and Entrepreneurs (SMEE), as a Sector, can take on a major role in agricultural development of the Republic of Serbia. However, in order to develop these enterprises, it is necessary to provide financial resources for their establishment and development, as well as appropriate business advisory support. This paper analyzes the issues regarding agribusiness companies financing, and interprets the use of advisory services. The aim of this analysis is to prove that small and medium-sized enterprises, entrepreneurs and farmers in particular, have limited access to financing and advisory services compared to larger companies. A survey that included 119 companies was conducted during this project. The obtained responses were stratified according to company size into three groups: entrepreneurs and farmers, small and medium-sized enterprises and large enterprises. The results showed that there were statistically significant differences between entrepreneurs and farmers, small, medium and large enterprises in most of the monitored parameters.